Phylogeny of the Neotropical sages (Salvia subg. Calosphace; Lamiaceae) and insights into pollinator and area shifts - Fragoso-Martínez, Itzi (2018)
Salvia subg. Calosphace (Lamiaceae, Lamiales) is a highly diverse clade endemic to the New World. The phylogenetic relationships of Calosphace have been previously investigated using DNA sequences of nuclear ITS region and plastid psbA–trnH intergenic spacer, but the resulting trees lack resolution and support for many clades. The present paper reassesses the phylogenetic relationships of subgenus Calosphace, including a broader taxon sampling, with a special focus on representing previously unsampled sections, and using an additional plastid marker (trnL–trnF region). Our results show increased resolution and overall patterns of support, recovering ten main clades. Within core Calosphace, the most inclusive of these main clades, 17 new subclades were identified. Of the 42 sections for which more than one species was analysed, only 12 are monophyletic. Our biogeographical analysis identified at least twelve migrations to South America from Mexican and Central American lineages, in agreement with previous suggestions of multiple origins of South American Calosphace diversity. This analysis also confirmed a colonization of the Antilles by Andean lineages. The reconstruction of ancestral states of pollination syndromes showed multiple shifts to ornithophily from melittophily and one reversal to the latter.